The use of derivational affixes in colours magazine by garuda indonesia - Sari, Ni Wayan Eka Mustika; Sulatra, I Komang; Putra, I G B Wahyu Nugraha (Journal of Language and Applied Linguistics, 2020)
This study concerned with the derivational process found in the Colours Magazine by Garuda Indonesia. The study aimed to find out the types of derivational process found in the Colours Magazine by Garuda Indonesia. This study collected the data through library research. This study used descriptive quantitative and qualitative method to describe and analyze the data. The theory proposed by Katamba (1993) is used to analyze the types of derivational process and Mc Charty’s (2002) theory is used to analyze how the function of derivational process used in this study. Formal and informal method used to present the data in this study. Based on the result, there were two types of derivational process found in this study namely un-, en- for derivational prefixes and able,-al, -ed, -er, -ful, -ing, -ion, -ity, -ive, -ly, -ment, -y for derivational suffixes. This study found 90 data of derivational affixes. There are 4 data (4.4%) of derivational prefixes and 86 (95.6%) data of derivational suffixes. This study concludes that derivational suffixes is the most dominant type of derivational affixes that found in the Colours Magazine by Garuda Indonesia.